The Correlation between Spiritual Well-Being and Burnout of Teachers - Pong, Hok-Ko (Religions, 2022)
This study examines the correlation between spiritual well-being and burnout symptoms, including emotional exhaustion (EE), depersonalisation (DP), and personal accomplishment (PA), among Chinese secondary school teachers in Hong Kong. The data were collected from 427 Chinese secondary school teachers (189 males, 238 females) aged 25–37 from different schools with one to eight years of teaching experience. The participants completed the Spiritual Health and Life-orientation Measure (SHALOM) to evaluate the status of their spiritual well-being in the personal and communal, environmental, and transcendental domains. The Maslach Burnout Inventory—Human Services Survey (MBI-HSS) was also used to measure the extent of burnout in the workplace. All domains of spiritual well-being were negatively associated with EE and DP, while the personal and communal domain and the transcendental domain of spiritual well-being were positively associated with PA. Multiple regression analysis revealed that all the specific domains of spiritual well-being explained 68.6% and 54.0% of the variance in teachers’ EE and DP, respectively. Meanwhile, the same analysis found that the personal–communal and transcendental domains explained 74.9% of the variance in teachers’ PA. The personal–communal domain of spiritual well-being was the strongest predictor of burnout.